Development of interactive multimedia in improving the ability to think logically in cell concepts - Saiman Rosamsi; Mieke Miarsyah; Rizhal Hendi Ristanto; Nia Nurdiani (JPBIO (Jurnal Pendidikan Biologi), 2023)
This research is motivated by educators who do not optimize learning media in teaching biology in high school, so this will have an impact on students' thinking skills at a concrete level. This study aims to develop learning and the application of multimedia to improve students' thinking power. This study uses the Borg and Gall development model through the stages of research and information gathering, planning, initial product development, initial field trials, main product revisions, main field trials, product revision operations, operational field trials, final product revisions, outreach, and implementation. Follow-up research combined with quasi-experimental research. This multimedia validation involves media experts, content experts, and linguists as well as students. The research instrument used was in the form of multiple-choice questions. The development results have been assessed by expert judgment. The developed multimedia learning can be used well at the high school level in Class XI IPA and is classified as very good. The results obtained for improving students' thinking skills in biology learning can be used in the learning process by obtaining the results of increasing students' thinking skills.